2018
DOI: 10.1136/bjophthalmol-2018-312055
|View full text |Cite
|
Sign up to set email alerts
|

Synthetic biodegradable alternatives to the use of the amniotic membrane for corneal regeneration: assessment of local and systemic toxicity in rabbits

Abstract: AimThe aim of this study was to assess the local and systemic response to poly-lactic co-glycolic acid (PLGA) 50:50 membranes, developed as synthetic biodegradable alternatives to the use of human donor amniotic membrane in the treatment of limbal stem cell deficiency.MethodsPLGA membranes of 2  cm diameter and 50  µm thickness were placed on one eye of rabbits and secured in place using fibrin glue and a bandage contact lens, suturing the eye close with a single stitch. Control animals were treated identicall… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
13
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 19 publications
2
13
0
Order By: Relevance
“…This was confirmed in a prior study in rabbits where we looked for any evidence of topical or systemic toxicity. 18 This finding is consistent with the current report in humans.…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…This was confirmed in a prior study in rabbits where we looked for any evidence of topical or systemic toxicity. 18 This finding is consistent with the current report in humans.…”
Section: Discussionsupporting
confidence: 94%
“…15 Toxicology studies in rabbits confirmed the absence of local or systemic toxic effects and showed that the membranes disappeared completely within 28 days. 18 After these satisfactory preclinical studies, our next step was to conduct a proof-of-concept trial in man. The study objectives were to assess the performance of the PLGA membranes in terms of their safety (primary outcome) and efficacy (secondary outcome) in restoring the health of the ocular surface and vision in patients with LSCD.…”
Section: Key Messagesmentioning
confidence: 99%
“…[51,232,248] These materials have better strength and degradation resistance than many natural polymers, however in most cases the materials lack transparency; therefore, sufficient spacing is required between fibers to allow light to pass through. Rather than generating full thickness corneal scaffolds, synthetic polymers are more suitable for generating thin electrospun sheets for epithelial [248b,d] or endothelial [248a] transplantation, as an alternative to amniotic membranes [249] or as mechanical support for a stromal hydrogel material. [51] Natural polymers including gelatin and collagen have been investigated for use in generating scaffolds for corneal regeneration.…”
Section: Electrospinningmentioning
confidence: 99%
“…AM is one of the thickest basement membranes that exists in the human body, with the ability to promote epithelial cell healing, besides inhibiting fibroblast proliferation and myofibroblast differentiation. In addition, it contains several anti-angiogenic, anti-inflammatory, and neurotrophic factors (Ramachandran et al, 2019). At present, AM transplantation has been used for various indications including repairing persistent epithelial defects and treating corneal ulceration, limbal stem cell deficiency, acute Stevens Johnson Syndrome (SJS), chemical and thermal burns, infectious keratitis, and after refractive surgery (St. Denis et al, 2012; Manolova et al, 2017; Prabhasawat, 2017; Westekemper et al, 2017).…”
Section: Corneal Wound Healingmentioning
confidence: 99%